2013
DOI: 10.1093/humrep/det389
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of ovarian activity by daily measurement of urinary excretion rates of oestrone glucuronide and pregnanediol glucuronide using the Ovarian Monitor, Part III: Variability of normal menstrual cycle profiles

Abstract: Financial support for this study was obtained from the UNDP/UNFPA/World Bank/WHO Special Programme of Research, Development and Research Training in Human Reproduction (HRP). D.G.C. is currently employed by and holds stock in Manawatu Diagnostics Ltd, a company in the development phase of a potentially competing product. The remaining authors have nothing to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 20 publications
0
35
1
2
Order By: Relevance
“…Using urinary samples, LH levels 2.1 to 61 times baseline levels were observed (38). New monitors that include urinary measurements of progesterone metabolites (24, 25) should help reduce the variability in assessment of ovulatory status; however, further research is needed to compare monitor performance to transvaginal ultrasound among larger cohorts of women (34). …”
Section: Discussionmentioning
confidence: 99%
“…Using urinary samples, LH levels 2.1 to 61 times baseline levels were observed (38). New monitors that include urinary measurements of progesterone metabolites (24, 25) should help reduce the variability in assessment of ovulatory status; however, further research is needed to compare monitor performance to transvaginal ultrasound among larger cohorts of women (34). …”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have compared urinary hormone profiles relative to each other, but not relative to the objective day of ovulation [13,14]. For example, a recent study by Blackwell et al looked at urinary hormone profiles of estrone glucuronide (EG), pregnanediol glucuronide (PdG) and luteinising hormone (LH), using a mixture of laboratory and home-based monitoring, and concluded that urinary hormone monitoring was a useful tool for cycle examination [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study by Blackwell et al looked at urinary hormone profiles of estrone glucuronide (EG), pregnanediol glucuronide (PdG) and luteinising hormone (LH), using a mixture of laboratory and home-based monitoring, and concluded that urinary hormone monitoring was a useful tool for cycle examination [14]. Other studies analysing serum hormone profiles have used the day of the LH peak to establish reference ranges [15], but this introduces relevant imprecision into the profiles, as it makes assumptions in timing of peak LH levels relative to ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, there are differences in hormonal patterns, even in ovulatory cycles, which introduce a further source of difficulty into the analysis [34,35]. This compromises the utility of all fertility awareness methods that solely rely on statistical parameters or calculation rules of the menstrual cycle (i.e.…”
Section: Discussionmentioning
confidence: 99%